Можно без полного решения, только верную идею

iznaur2002 iznaur2002    3   09.06.2019 08:10    0

Ответы
see99aa see99aa  08.07.2020 07:06
sin( \pi cosx)=sin( \frac{ \pi }{2}+ \pi sinx) \\ sin( \pi cosx)-sin( \frac{ \pi }{2}+ \pi sinx)=0 \\ 2sin( \frac{ \pi cosx- \frac{ \pi }{2}- \pi sinx }{2})cos( \frac{ \pi cosx-+\frac{ \pi }{2}-+\pi sinx }{2})=0 \\ sin( \frac{ \pi cosx- \frac{ \pi }{2}- \pi sinx }{2})=0 \\ cos( \frac{ \pi cosx+\frac{ \pi }{2}+\pi sinx }{2})=0
Из этого должно что-то получиться, по-моему
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра